Diversidade e biomassa da comunidade zooplanctônica e produção secundária (Cladocera e Rotifera) em pontos com influência do esgoto sanitário no reservatório da UHE de Furnas-MG, município de Alfenas e caracterização biológica de uma espécie de Cladocera - Viti, Thais (2013)
Because the reservoirs are part of a watershed, they receive the impact of all human surrounding activities. The dumping of sewage causes the increase of nutrients such as nitrogen and phosphorus, modifying profoundly the ecological balance of the environment. The aim of this study was to verify changes in diversity and biomass of zooplankton in four points located in UHE Furnas reservoir, but only one of these was not influenced by sewage. The physical, chemical and biological (chlorophyll a and zooplankton) of water were analyzed and biomass and production of zooplankton (Cladocera and Rotifera) were calculated. Also, the life cycle in two different treatments (one offering algae and the other food and other offering only algae), and molecular biology of a species of Cladocera were investigated. The physical and chemical parameters varied seasonally, as well as the nutrient concentrations during the study period. The sampling points, which were influenced by sewage, were considered eutrophic and the presence of some species (Bosmina freyi, Brachionus calyciflorus and Synchaeta jollyae), highest individual’s densities, secondary production and biomass values indicated this higher trophic state. Rotifera and Copepoda were abundant during the study period and Copepoda was the group of highest biomass. For zooplankton community, 103 taxa were identified, which show high species richness. According to the curves ABC, the points with higher influence of the sewage were considered as disturbed environments. Through analysis of the life cycle of C. rectangula, when this species was feed with algae only, was observed that it has a higher post-embryonic development time (3.51 days) and lower longevity (23.9 days), number of seedlings (10) and body size when compared as species that received richest food. Through molecular analysis was first characterized the DNA Barcode of C. rectangula, and this species showed higher nucleotide similarity with species of Leydigia and Kurzia genera. This analysis is unprecedented and may assist in clarifying the taxonomy of this species, since it is still uncertain.